Pengembangan Aplikasi “My Brascho” Untuk Mata Pelajaran Ekonomi di SMA Brawijaya Smart School - Syahrul Munir; Anang Setyo Santoso (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
This study aims to develop an ispring-based learning media which is expected to be a solution in learning economics material for national income according to student needs. The research method used by the researcher is research and development with a 4D model. The subjects in this study were students of class XI economics at SMA Brawijaya Smart School. The instruments used in research and development of this media were observation and questionnaires. Data analysis techniques used in testing learning media by expert validation, media validation, and small group trials. Then the data were analyzed using a descriptive percentage analysis technique. The result of the development is a learning media in the form of an android application that contains four components, namely materials, learning videos, quizzes, and profiles. The results of media and material validation show that the product is categorized as "fit for use". The results of the small group and large group trial in class XI-1 SMA Brawijaya Smart School showed similar results, meaning that the learning media was in accordance with the needs of students and was suitable for use in the economic learning process of national income materials.